Enhancement of persistent currents and magnetic fields in a two dimensional quantum ring - Vinod Prasad; Monika Arora; Varsha (Scientific Reports, 2023)
Abstract We present the study of the SiGe quantum ring (QR) modeled by an anharmonic axially symmetric potential with a centrifugal core in the effective mass approximation. We show how the femtosecond laser pulses (FLPs) can be used efficiently for controlling the induced current and magnetic field. We have compared the strength of induced currents and magnetic fields with and without pulsed laser which shows a substantial change. The spin-orbit interaction (SOI) and Zeeman energy show a massive impact on the generation and enhancement of these induced current and magnetic fields. These induced currents and magnetic fields have many applications in interdisciplinary areas. We have shown that the SOI presence with the FLP fields while competing with the confinement strength lowers the strength of the induced current and field.